Basic medical sciences should be mainly taught by clinicians for a tight integration of basic and clinical sciences in medical education. - Süleyman Oktar (Acta Medica Alanya)
Today, medical education faces many problems. However, the most serious problem is the inability to integrate basic and clinical sciences. For this reason, students alienate from basic sciences, and clinicians are leaving sciences to basic scientists every day. Basic medical sciences learned in the preclinical term are remembered less by students and cannot be sufficiently associated with clinical reality. This is because basic scientific knowledge learned without a clinical framework is low-value data that the student does not know how to use. Therefore, all reform initiatives in the medical education curriculum stick to the obstacle of basic sciences. Now is the time to take bold steps. The first step should be to remove the preclinical term from medical education. Medical education should only consist of clinical education terms. This will gain the student and clinician a lot more time for clinical training. The second step should be to take basic sciences education from basic scientists and place it under the responsibility of clinicians. Clinicians can decide much better how much of basic science knowledge is clinically relevant. As a component of clinical education, it is best for students to internalize the basic sciences during classes, at the bedside, and in other clinical practices under the clinician's authority. Thus, students may be graduated as academic clinicians who have internalized the basic sciences and integrated the basic sciences with clinical reality.